Injectable Hydrogel for Synergetic Low Dose Radiotherapy, Chemodynamic Therapy and Photothermal Therapy - Chen, Mingzhu; Wang, Ziqi; Suo, Weilong; Bao, Zhirong; Quan, Hong (Frontiers in Bioengineering and Biotechnology, 2021)
Higher doses of radiotherapy (RT) are associated with resistance induction, therefore highly selective and controllable radiosensitizers are urgently needed. To address this issue, we developed a FeGA-based injectable hydrogel system (FH) that can be used in combination with low-dose radiation. Our FH can deliver FeGA directly to the tumor site via intratumoral injection, where it is stored as a ration depot. The photothermal properties of FeGA steadily dissolve FH under laser irradiation, and, simultaneously, FeGA reacts with a large amount of H2O2 in the cell to produce ·OH (Fenton reaction) which is highly toxic to mitochondria, rendering the cell inactive and reducing radiotherapy resistance. In vivo and in vitro studies suggest that combining the FH and NIR irradiation with RT (2Gy) can significantly reduce tumor proliferation without side effects such as inflammation. To conclude, this is the first study to achieve combined CDT and PTT in situ treatment, and the best therapeutic effect can be obtained with a low-dose radiation combination, thus expanding the prospects of FeGA-based tumor therapy.